The Value of Financial Analysis Information: Theoretical View - Mackevičius, Jonas; Raziūnienė, Daiva; Valkauskas, Romualdas (Buhalterinės apskaitos teorija ir praktika, 2020)
The value of financial information analysis depends on usability, efforts, duration, etc. These dimensions have not been systematically reviewed as well as assessment methods have not been established yet. The purpose of the article is an examination of value dimensions and arrangement of the model for identifying and determining analysis methods. Research methods of this article are literature analysis, classification, specification and generalization of information. In this article, we focus on financial analysis data and the relation between information and its value. We suggest the theoretical model which determines dimensions of the information value and costs related to its transfer. We propose a method of evaluating parameters of value and how these parameters may influence its exposure.